Analisis penerapan prinsip Mayer pada multimedia digital dalam pembelajaran matematika di kelas IV sekolah dasar - Puji Rahayu; Sri Marmoah; Tri Budiharto (Didaktika Dwija Indria, 2024)
The world of education has undergone significant changes due to the development of information and communication technology. One impact of these changes is the use of digital multimedia in the learning process. This study aims to describe and understand the application of Mayer's principles in digital multimedia for mathematics learning in Grade IV of SD Muhammadiyah Plus Salatiga in the academic year 2023/2024. This research used a qualitative approach with a case study method. Data were collected through interviews, observations, and documentation. The subjects were teachers and Grade IV students at SD Muhammadiyah Plus Salatiga. The results obtained regarding the application of Mayer's cognitive multimedia principles in digital multimedia for learning in Grade IV of SD Muhammadiyah Plus Salatiga revealed ten principles applied in digital multimedia. These principles are contiguity, spatial contiguity, temporal contiguity, coherence, redundancy, signaling, segmenting, multimedia, personalization, and interactivity.